Art and activism in the age of systemic crisis : aesthetic resilience - Steinbock, Eliza, 1980-; Ieven, Bram; Valck, Marijke de (Routledge, 2021)
"This book examines how renewed forms of artistic activism were developed in the wake of the neoliberal repression since the 1980s. The volume shows the diverse ways in which artists have sought to confront systemic crises around the globe, searching for new and enduring forms of building communities and reimagining the political horizon. The authors engage in a dialogue with these artistic efforts and their histories - in particular the earlier artistic activism that was developed during the civil rights era in the 1960s and 70s - providing valuable historical insight and new conceptual reflection on the future of aesthetic resilience. This book will be of interest to scholars in contemporary art, history of art, film and literary studies, protest movements, and social movements"-- Provided by publisher.
Keywords: Arts -- Political aspects.; Art and social action.; Art et action sociale.; Arts -- Aspect politique.; ART / Art & Politics; ART / History / Contemporary (1945-); POLITICAL SCIENCE / Political Process / Political Advocacy; Art and social action; Arts -- Political aspects; Electronic books.